Intention Of Muslim And Non-Muslim Indonesian Investors In Investing In Retail Sukuk - Slamet, Kuwat; Riestianty, Riestianty; Budiyono, Budiyono (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
This study aims to analyze the factors that influence the intention of individual investors, both Muslim and non-Muslim, to invest in Retail Sukuk issued by the Indonesian government using the Theory of Planned Behavior (TPB). This study is quantitative research. Data was obtained by distributing questionnaires that had previously been tested to ensure their validity and reliability. The participant data was processed by 214 participants who came from various levels of society and various cities in Indonesia. Furthermore, the data was processed using the Microsoft Excel application and the Smart PLS-SEM application version 3.3.3. The results show that the intentions of Muslim investors and non-Muslim investors are both significantly determined by their attitude toward investing, subjective norms that exist within them, and perceptions of behavioral control. The government considers the results of this research as input for determining the right strategy to expand the retail sukuk investor base, both Muslim and non-Muslim investors in Indonesia. The limitations of this study are the number of participants which is quite small.